Pengembangan Butir Soal Literasi Kimia pada Materi Ikatan Kimia Menggunakan Model Rasch - Muhammad Rizki; Eka Yusmaita (Edukimia, 2021)
This study aims to develop chemical literacy items on chemical bonding material that can be used to measure students literacy skills, help students understand chemical literacy-based questions, understand chemistry, communicate chemistry orally and in writing, and apply their ability to solve problems in daily life. The type of research is development research with Model of Educational Reconstruction (MER) design. The content validity test was carried out by five validators and analysed using the Rasch model with the facets application. Meanwhile, empirical testing of students was analysed using the Rasch model with the winsteps application. The results of the content validity analysis in this study showed the results of the agreement (exact agreements) of 86,8 percent and the estimated results of the approval (expected agreements) of 87,8 percent, and the results of the analysis of chemical literacy instruments had a valid category and had a reliability value of 0,96.